2017
DOI: 10.3390/met7110476
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Characterization of Inconel 718 Post-Dynamic Recrystallization within a Scanning Electron Microscope

Abstract: Microstructure evolution within the post-dynamic regime following hot deformation was investigated in Inconel 718 samples with different dynamically recrystallized volume fractions and under conditions such that no δ-phase particles were present. In situ annealing treatments carried out to mimic post-dynamic conditions inside the Scanning Electron Microscope (SEM) chamber suggest the occurrence of both metadynamic and static recrystallization mechanisms. Static recrystallization was observed in addition to met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…After compression, the specimen was held for more than 5 s to leave time for post‐dynamic evolutions to occur, and then water quenched. The PDRX kinetics are indeed known to be very fast, and 5 s holding time after deformation should be enough to get a significant evolution (Na et al ., ; Zouari et al ., ). Following this procedure, the final microstructure should thus encompass both DRX and PDRX grains.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…After compression, the specimen was held for more than 5 s to leave time for post‐dynamic evolutions to occur, and then water quenched. The PDRX kinetics are indeed known to be very fast, and 5 s holding time after deformation should be enough to get a significant evolution (Na et al ., ; Zouari et al ., ). Following this procedure, the final microstructure should thus encompass both DRX and PDRX grains.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…The variations of average GND density, SSD density, and average hardness in the mixed microstructure can qualitatively represent changes in the dislocation and hardness of the prior austenite grains [31,32]. [15], a sole SRX process occurred in sample A when the interruption strain was lower than the critical strain [11]; however, only MDRX was observed in sample B because the rapid MDRX quickly consumed all available stored dislocations before SRX could occur [16]. With the aid of the SPM, the indentation arrays were found to be located in the center of the deformed grains and recrystallized grains (including dynamically recrystallized grains, SRX grains, and MDRX grains), as shown in Figure 2a.…”
Section: Hardness Testsmentioning
confidence: 99%
“…Studies have shown that the softening phenomena during post-deformation annealing can be attributed to the MDRX and SRX process [12][13][14][15][16][17]. Djaic and Jonas [12] first proposed the concepts of SRX and MDRX and designed several double-pass compression experiments to distinguish the softening effects caused by these two varieties of recrystallization regimes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo [5] investigated the high-temperature softening characteristics of dynamic recrystallization and dynamic recovery during high-temperature deformation and proposed optimal hot forging conditions. In addition, Lee [6] and Zouari [7] proposed a process method for lowering the strain resistance of SPF8090 Al-Li and for the grain refinement of Inconel 718. Bang [8] and Cho [9] offered a method to predict the forming load and microstructure during the high-temperature deformation of carbon steel.…”
Section: Introductionmentioning
confidence: 99%